2014
DOI: 10.1097/mao.0000000000000435
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes in Cystic Vestibular Schwannoma Versus Solid Vestibular Schwannoma

Abstract: The difference in surgical outcomes is minimal between patients with CVS and those with SVS, not reaching statistical significance. We think, with judicious surgical management, similar outcomes can be achieved in cystic tumors and solid tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 19 publications
2
19
2
1
Order By: Relevance
“…Numerous studies have reported worse outcomes with cystic tumors compared with solid tumors and recommend STR when GTR is not feasible. [30][31][32][33][34][35][36][37] Also, this study did not consider intracanalicular extension nor bony changes to the IAC as they have been reported to be insignificant factors for predicting FN outcome. 13,14,17,38 Additionally, increased overall tumor volume has also been linked to worse FN outcomes, as one would expect, but it is still uncertain whether tumor volume is more predictive than maximum tumor diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported worse outcomes with cystic tumors compared with solid tumors and recommend STR when GTR is not feasible. [30][31][32][33][34][35][36][37] Also, this study did not consider intracanalicular extension nor bony changes to the IAC as they have been reported to be insignificant factors for predicting FN outcome. 13,14,17,38 Additionally, increased overall tumor volume has also been linked to worse FN outcomes, as one would expect, but it is still uncertain whether tumor volume is more predictive than maximum tumor diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Cystic vestibular schwannnoma (CVS) should be distinguish from solid vestibular schwannoma (SVS) because of the their variant clinical, radiological, histopathological features and surgical outcomes. 2 , 3 , 4 , 5 CVS can be peripherally located thin-walled tumors, and centrally located thick-walled tumors based on CT or MRI images. CVS frequently presents rapid progression of symptoms with facial nerve involvement.…”
Section: Nomenclaturementioning
confidence: 99%
“…Some authors reported its association with worse outcomes, 10 whereas others showed no difference between cystic and solid tumors when considering facial nerve outcomes after surgery. 11 Tumor adhesion is also reported to be a factor influencing facial nerve outcomes. 9,12 In this context, we conducted a retrospective study of patients who were operated for total resection of vestibular schwannoma with anatomic preservation of the facial nerve.…”
mentioning
confidence: 99%